Risk Assessment and Grading of Environmental Sustainability of the International Wetlands of Southern Coasts of Iran - Samira Jafari Azar; Gholam Reza Sabzghabaei; Morteza Tavakoli; Soolmaz Dashti (مخاطرات محیط طبیعی, 2020)
Wetlands are sensitive and valuable ecosystems but today their safety and their sustainability have been harshly influenced by various natural and human factors. Using environmental risk assessment is an important tool in studies of environmental management and recognition and reduction of the potentially harmful environmental factors to achieve sustainable development. This research was conducted to identify and assess the risks and grading of environmental sustainability of the international wetlands of the southern coast of Iran in the provinces of Khuzestan and Hormozgan. Accordingly, to identify and prioritize the risks  the Delphi methodology, to prioritize and calculate the weight of the indicators the Analytical Hierarchy Process (AHP) process, and the ELECTRE technique were used to rank the wetlands based on unfavorable environmental conditions. The results showed that 27 factors of pressure and threat were identified for The International Wetland of Shadegan, Khur_e_ Omayyeh and Khur_e_Mousa Estuary, Khur-e-khuran International wetland, Salty, Sweet and Minab Rivers International Wetlands, Gaz and Hara Rivers Estuary International wetland and Shidvar International Wetland. The results of the paired comparisons between the threats of the studied wetlands show that the first to fifth ranking threats are related to the discharge and disposal of waste in the wetland, climate change and drought, oil pollution, dam construction, and the reduction of vegetation density, and other indicators are in the next ranks. Finally, the analysis and comparison for the ranking of the studied wetlands based on the ELECTRE method showed that The International Wetland of Shadegan, Khur_e_ Omayyeh and Khur_e_Mousa Estuary suffer the highest threat and pressure and Shidvar International Wetland has a more favorable ecological condition.